LEGALITAS PENGUSAHA MIKRO KECIL MENENGAH DALAM PROGRAM PEMBERDAYAAN USAHA OLEH KANTOR PERWAKILAN BANK INDONESIA BANTEN - Buana, Tri; Wijaya, Pringgo A; Maulana, Ayang Fristia; Faturrohman, Faturrohman (LPPM Universitas Bina Bangsa, 2024)
Guidance for Micro, Small and Medium entrepreneurs in the form of providing facilities, guidance and assistance in order to develop the entrepreneurs' businesses. The birth of Micro, Small and Medium entrepreneurs who have potential but do not yet have complete business legality. Bank Indonesia offers development and empowerment programs for small and medium entrepreneurs. Bank Indonesia Banteb participates in the development of Micro, Small and Medium Enterprises by issuing Micro, Small and Medium Enterprises and Real Sector development programs from the Bank Indonesia Entrepreneur Association (WUBI), cluster programs and others related to product development for Micro, Small and Medium Enterprises. In empowering UMKM (Micro, Small and Medium Enterprises), actors experience various obstacles, namely inadequate knowledge of human resources, insufficient capital and minimal knowledge of product marketing